Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1186/s12935-021-01912-0
|View full text |Cite
|
Sign up to set email alerts
|

LINC01783 facilitates cell proliferation, migration and invasion in non-small cell lung cancer by targeting miR-432-5p to activate the notch pathway

Abstract: Background Non-small cell lung cancer (NSCLC) is a common malignancy around the globe. Increasing long non-coding RNAs (lncRNAs) have been confirmed to be associated with the progression of cancers, including NSCLC. Long intergenic non-protein coding RNA 1783 (LINC01783) is a novel lncRNA and its regulatory function as competing endogenous RNA (ceRNA) has not been studied in NSCLC. Methods RT-qPCR measured the expression level of LINC01783 in NSCLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…It is acknowledged that the controlled expression of miRNAs is indispensable for normal cells, while the aberrant expression of miRNAs may lead to diseases, including cancers [52,53]. As reported, miR-432-5p could be regarded as a tumor inhibitor in human cancers; for example, DRAIC could promote the growth of breast cancer by sponging miR-432-5p to upregulate SLBP [54], circ-ZNF609 could target miR-432-5p to regulate the expression of LRRC1 to promote cholangiocarcinoma [55], and LINC01783 could facilitate cell proliferation, migration and invasion in non-small cell lung cancer by targeting miR-432-5p [56]. However, the underlying function of miR-432-5p in TNBC has not been reported.…”
Section: Discussionmentioning
confidence: 88%
“…It is acknowledged that the controlled expression of miRNAs is indispensable for normal cells, while the aberrant expression of miRNAs may lead to diseases, including cancers [52,53]. As reported, miR-432-5p could be regarded as a tumor inhibitor in human cancers; for example, DRAIC could promote the growth of breast cancer by sponging miR-432-5p to upregulate SLBP [54], circ-ZNF609 could target miR-432-5p to regulate the expression of LRRC1 to promote cholangiocarcinoma [55], and LINC01783 could facilitate cell proliferation, migration and invasion in non-small cell lung cancer by targeting miR-432-5p [56]. However, the underlying function of miR-432-5p in TNBC has not been reported.…”
Section: Discussionmentioning
confidence: 88%
“…We predicted that miR-15a-5p may silence gene expression, inhibit the apoptosis pathway, and play an important role in promoting cell proliferation. It is reported that LINC01783 may increase in NSCLC cell lines, and down-regulation of LINC01783 suppressed cell proliferation, migration, and invasion by regulating Notch pathway and sponging miR-432-5p ( Deng et al, 2021 ). Guo et al found that Notch2 may negatively regulate cell invasion by inhibiting the PI3K-Akt signaling pathway in gastric cancer ( Guo et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the second pathway, SNHG11 directly binds to β -catenin and activates the WNT pathway ( Liu et al, 2020 ). A novel long intergenic non-protein coding RNA (LINC01783) that suppresses miR-432-5p, a route that results in non-small cell carcinogenesis, activates the NOTCH pathway to increase DLL-1 expression and enhances the proliferation of NSCLC cells ( Deng et al, 2021 ) ( Table 1 ).…”
Section: Epigenetic Regulation Of Stem Cells In Lung Cancer Oncogenesismentioning
confidence: 99%